2019
DOI: 10.3389/fpsyg.2019.00415
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Dyadic Coping on the Marital Adjustment of Couples Undergoing Assisted Reproductive Technology (ART)

Abstract: A couple is considered to be infertile if unable to conceive after 12 months of unprotected sexual intercourse. An extended body of literature supports that infertility and infertility treatments contribute to emotional, social, sexual, and relational issues that can have a negative impact on each partner's well-being and on the couple relationship. Recent findings suggest that a dyadic approach should be used when working with couples coping with these stressors. However, most research to date has focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 83 publications
4
40
0
1
Order By: Relevance
“…The inverse relation of women's using of GR strategy with negative psychological symptoms and positive relation of men's using of MD strategy with their anxiety level are the other findings of this research. These results are in direction of the other researches reports which have shown the positive effects of using this strategy in faced with the crisis in men and women [21,22]. Also, the inverse effects of using avoidance strategies on psychological health of infertile couples have already been reported [12,23], but despite these reports, in the present research there was no significant relationship between women's using of avoidance strategy and their psychological health indices.…”
Section: Discussionsupporting
confidence: 65%
“…The inverse relation of women's using of GR strategy with negative psychological symptoms and positive relation of men's using of MD strategy with their anxiety level are the other findings of this research. These results are in direction of the other researches reports which have shown the positive effects of using this strategy in faced with the crisis in men and women [21,22]. Also, the inverse effects of using avoidance strategies on psychological health of infertile couples have already been reported [12,23], but despite these reports, in the present research there was no significant relationship between women's using of avoidance strategy and their psychological health indices.…”
Section: Discussionsupporting
confidence: 65%
“…DC has been shown to be beneficial for couples facing a wide range of stressors such as breast cancer (Kraemer, Stanton, Meyerowitz, Rowland, & Ganz, 2011), infertility (Molgora et al, 2019) or daily stress (Falconier, Nussbeck, Bodenmann, Schneider, & Bradbury, 2015; Merz, Meuwly, Randall, & Bodenmann, 2014). Moreover, DC is associated with relationship stability (Ruffieux et al, 2014).…”
Section: Relationship Behaviors and Couples’ Satisfactionmentioning
confidence: 99%
“…In addition, although research increasingly emphasizes that infertility condition may have a significant impact on both partners of infertile couples, some gender differences were also reported (e.g., Berghuis and Stanton, 2002 ; Ying et al, 2015 ; Molgora et al, 2019 ). However, whether the majority of studies underlined that women perceive higher levels of infertility-related stress ( Cserepes et al, 2013 ; Luk and Loke, 2015 ) and anxiety ( El Kissi et al, 2013 ; Ying et al, 2015 ; Schaller et al, 2016 ), mixed evidence on gender differences in coping strategies were found.…”
Section: Introductionmentioning
confidence: 99%